VARIABEL-VARIABEL PENENTU HOLDING PERIODSAHAM - Kadek Aryati, Margaretha; Ni Nyoman Ayu, Diantini (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 9 Nomor 1 Tahun 2015, 2015)
This study was conducted to determine the effect of the bid-ask spread, market value risk of return and earnings per share (EPS) on the holding period of the stock index LQ45 during 2011-2013. This study used a non-participant observation method to view the report published on the Stock Exchange’s website (www.idx.co.id) and using the bid - ask price data dof Indonesian Capital Electronic Library (ICamel). This study used a sample of 25 companies drawn by the purposive sampling method. The data analysis technique used is multiple linear regression. The results of this study indicate that  out of four independent variables considered in this study i.e. bid-ask spread, risk of return, EPS, and market value, only market value has significant effect  on holding period of the stock index LQ45 period 2011- 2013.
Keywords: holding period, bid-ask spread, market value, risk of return, earning per share